Collagenous Inflammatory Mucosal Diseases of the Gastrointestinal Tract - Hugh J Freeman (Canadian Journal of Gastroenterology)
A new group of collagenous inflammatory disorders of the gastric and intestinal mucosa has been described in the past two decades. These entities appear to be characterized by a distinct histopathologic lesion in the subepithelial region of the lamina propria. Functional alterations may also occur, presumably related to collagen deposition and the associated inflammatory process. Collagenous sprue is characterized by progressive and unrelenting malabsorption; a lethal outcome has usually been described, possibly reflecting the site of collagen deposition and the critical role of the small bowel for maintenance of a normal nutritional state. In contrast, collagenous colitis is characterized by persisting or episodic watery diarrhea; clinical impairment appears to be less severe but the entity is not rare, possibly reflecting its colonic localization. Most recently, collagenous gastritis, possibly accompanied by a functional reduction in acid secretion and impaired gastric emptying, has been recognized. Further definition of these entities is still required, particularly in relation to etiology, pathogenesis and effective therapy.